Bioenergy Research: Evaluating Strategies for Commercialization and Sustainability - Srivastava N.; Srivastava M. (My University, 2025)
Bioenergy Research offers an authoritative guide to recent developments in green bioenergy technologies that are currently available including: bioethanol, biobutanol, biomethanol, bio-oil, biohydrogen, biogas and biomethane. The authors provide in-depth analysis and discuss the commercial viability of the various technological advances in bioenergy. Comprehensive in scope, the book explores the environmental, practical and economic implications associated with a variety of bioenergy options. The book also considers the rollback of fossil fuels, the cost and their replacement as well as practical solutions for these issues. This important resource: Presents up-to-date research and industrial developments for various bioenergy options Offers comparative evaluation of bioenergy technologies for commercial feasibility Reviews current challenges and sustainable solutions for a variety of biofuel technologies Contains a review of existing strategies for bioenergy production Bioenergy Research is a valuable guide for academic researchers and industrial scientists working in the fields of biofuels and bioenergy, environmental science and technology, microbial technology, bioprocess engineering, and waste valorization. © 2021 by John Wiley & Sons Ltd. All rights reserved.